COVID-19: Lessons and emerging theories in Ayurveda - J Nandeesh (Wolters Kluwer Medknow Publications, 2020)
Background: The current pandemic situation of COVID-19 has given an opportunity to explore the traditional medicines around the globe. Ayurveda, being the front runner among the traditional knowledge, has a key role to overcome the situation. It has a distinct advantage of approaching the disease from various perspectives such as principle-based approach and diagnosis-based approach. A pandemic situation like COVID-19 can be considered under various concepts such as janapadodhvamsa and aupasargika roga as per Ayurveda. During the initial wave of COVID-19 infection, the uncertainty of the pathological considerations and legal restrictions limited Ayurveda to the preventive strategy by modulating the immune system of the body. Gradually, there is a shift from preventive to curative approach in Ayurveda, owing to unsatisfactory results from the contemporary medicine. The management protocol has expanded by not only concentrating on the yuktivyapashraya cikitsa (internal medicines). Several methods of daivavyapashraya and sattvavajaya cikitsa (measures to improve the psychological and social well-being) are adopted which include social norms as well as dietary regimen. Trisutra theory of Ayurveda, i.e., hetu (cause), linga (clinical features), and aushadha (management) is well utilized to frame therapeutic guidelines. Materials and Methods: Classical Samhita is referred focusing mainly on Caraka Samhita and Sushruta Samhita. Information related to diseases affecting a larger population at the same time is compiled. The references obtained are presented in terms of roga pareeksha vidhi. Results: Attempt is made to analyze the present pandemic in classical terms. Discussion and Conclusion: Classical references can be very well used to understand the pathological aspects of pandemic like COVID-19. Role of larger community role is inevitable in the occurrence of pandemic and following Ayurveda lifestyle definitely prevents them.